Dynamics of Lingulodinium polyedra Development in the Bulgarian Part of Black Sea (1992–2022) - Daniela Klisarova; Dimitar Gerdzhikov; Petya Dragomirova; Nina Nikolova; Martin Gera; Petya Veleva (Diversity)
Long-term data on the phytoplankton of the Bulgarian Black Sea (BBS) coast describe three states for the ecosystem: a “pristine” reference phase (1954–1970 years); an intensive anthropogenic eutrophication (1970–1992 years) phase; and a post-eutrophication phase after the early 1990s of the 20th century. The eutrophication period is characterised by ecosystem degradation and intense phytoplankton blooms, some of which were formed by the potentially toxic species Lingulodinium polyedra. This warm-water species is a red tide former that is associated with fish and shellfish mortality events. In the 1980s, L. polyedra reached the highest biomass of 84.4 g·m−3 in Varna Bay, BBS. The aim of this study (1992–2022) was to provide an overview of the development of L. polyedra in the phytoplankton biocenosis in the Bulgarian part of the Black Sea, taking into account the influence of anthropogenic stress and the climatic variables NAO and SST on the development of the species population. An analysis of the distribution of the dinoflagellate L. polyedra is based on a total of 5126 phytoplankton samples collected during the period between 1992 and 2022 under projects led by the Institute of Fish Resources, Varna. The samples were analyzed using standard methods validated for the Black Sea, and phytoplankton abundance and biomass were determined. The species are most abundant in summer in the coastal marine areas exposed to anthropogenic influence. During the analyzed period, a decrease in the abundance and biomass of L. polyedra in Bulgarian Black Sea waters were observed. It was found that the influence of climatic factors such as NAO and SST on the species population is from weak to moderate, and the correlation with NAO cycles is better expressed.